Sexual behavior among high school students in Brazil: alcohol consumption and legal and illegal drug use associated with unprotected sex (Clinics, 2013)
OBJECTIVE: Alcohol and other drug use appears to reduce decision-making ability and increase the risk of unsafe sex, leading to possible unplanned pregnancies, sexually transmitted diseases/human immunodeficiency virus/HIV transmission, and multiple sexual partners. This study aimed to test the hypothesis that risky sexual behaviors among adolescents are associated with legal and illegal drug use. METHODS: A national cross-sectional survey of 17,371 high-school students was conducted in 2010. Students were selected from 789 public and private schools in each of the 27 Brazilian state capitals by a multistage probabilistic sampling method and answered a self-report questionnaire. Weighted data were analyzed through basic contingency tables and logistic regressions testing for differences in condom use among adolescents who were sexually active during the past month. RESULTS: Approximately one third of the high school students had engaged in sexual intercourse in the month prior to the survey, and nearly half of these respondents had not used a condom. While overall sexual intercourse was more prevalent among boys, unsafe sexual intercourse was more prevalent among girls. Furthermore, a lower socioeconomic status was directly associated with non-condom use, while binge drinking and illegal drug use were independently associated with unsafe sexual intercourse. CONCLUSION: Adolescent alcohol and drug use were associated with unsafe sexual practices. School prevention programs must include drug use and sexuality topics simultaneously because both risk-taking behaviors occur simultaneously.